Rocuronium versus suxamethonium for rapid sequence induction of general anaesthesia for caesarean section: influence on neonatal outcomes. (November 2017) - Kosinova, M.; Stourac, P.; Adamus, M.; Seidlova, D.; Pavlik, T.; Janku, P.; Krikava, I.; Mrozek, Z.; Prochazka, M.; Klucka, J.; Stoudek, R.; Bartikova, I.; et al.
Highlights: This is an extension study of a previous publication. Women were randomised to receive rocuronium or suxamethonium for caesarean section. There were more 1-min Apgar scores <7 with rocuronium. There were no differences in 5-min or 10-min Apgar scores. There were no significant differences in umbilical arterial blood gases. Abstract: Background: In a previous study we compared rocuronium and suxamethonium for rapid-sequence induction of general anaesthesia for caesarean section and found no difference in maternal outcome. There was however, a significant difference in Apgar scores. As this was a secondary outcome, we extended the study to explore this finding on a larger sample. Methods: We included 488 parturients of whom 240 were women from the original study. Women were randomly assigned to receive either rocuronium 1 mg/kg (ROC n=245) or suxamethonium 1 mg/kg (SUX n=243) after propofol 2 mg/kg. Anaesthesia was maintained with up to 50% nitrous oxide and up to one minimum alveolar concentration of sevoflurane until the umbilical cord was clamped. We compared neonatal outcome using Apgar scores and umbilical cord blood gases. Results: Data were analysed for 525 newborns (ROC n=263 vs. SUX n=262). There was a statistically significant difference in the proportion of Apgar scores <7 at 1 min (ROC 17.5% vs. SUX 10.3%, P =0.023) but no difference at 5 min (ROC 8% vs. SUX 4.2%, P =0.1) or 10 min (ROC 3.0% vs. SUX 1.9%, P =0.58). There was no difference between groups in other measured outcomes. Conclusion: The use of rocuronium was associated with lower Apgar scores at 1 min compared with suxamethonium. The clinical significance of this is unclear and warrants further investigation.